Pengaruh Training Soft skill dan Komunikasi Terhadap Kinerja Karyawan UMKM di Cikarang - Aleng; Shima, Putri; Permatasari, Nur Intan (DPPM Universitas Pelita Bangsa, 2023)
This study aims to analyze the influence of variables Training Softskill, and Communication on Employee Performance. The analysis method used in this study is to use saturated sampling techniques. The type of data used is primary data obtained through a structured form using a questionnaire filled out by 30 people in one of the MSMEs. The analysis has met the requirements of analysis based on normally distributed data and there is no multicollinearity problem. Based on the output table